Making sense of problems in primary headship - Dunning, Gerald; Elliott, Tony (Bingley, U.K. : Emerald Publishing Limited, 2019)
Managing problems has always been a major responsibility of headship, but a substantial number of primary heads now regard their role as especially problematic. With a steadily expanding set of responsibilities and an increasingly demanding set of constituencies to satisfy, the problems which impinge upon primary headship seem set to become ever more challenging.While media sources regularly report increasingly onerous headteacher workloads, ever more rigorous accountability and responsibility demands and over-stretched school budgets, there has been very little empirical research into the problematic nature of modern primary headship. By using evidence from interviews with seventy primary headteachers, this book highlights the most serious problems experienced by primary heads. In particular, the management of school finance and premises and relationships with a range of other people involved in the life and work of the school are shown to be recurring historical issues in primary headship. This book is a response to these problems and draws upon research on organizational value theory, micropolitics and symbolism as well as school leader succession and socialisation studies. By offering a set of conceptual tools to enhance analysis of problem causes and identification of relevant management strategies this text will prove a valuable resource for researchers and leaders in education.
Prelims -- Introduction -- Part I: What's the problem? -- Chapter 1 Mapping the minefield: explaining the research studies -- Chapter 2 Landmarks in the minefield: generic problem issues -- Chapter 3 New heads on their blocks: the problems of assuming headship -- Chapter 4 Hard labour: managing a problematic workload -- Chapter 5 Close encounters: problematic colleagues -- Chapter 6 Clients and consumers: problematic parents and pupils -- Chapter 7 More checks than balances: problematic partners in school governance -- Chapter 8 Counting the cost: the personal impact of headship -- Part II: What every head should know -- Chapter 9 Making sense of headship: knowing what -- Chapter 10 Making sense of headship: knowing how -- Chapter 11 Back to the future: revisiting classic knowledge bases for problem analysis and framing -- Chapter 12 Learning the ropes? On the ropes? Making sense of headteacher succession and socialisation -- Chapter 13 Putting problems in perspective: strategy and reflection in problem management -- Chapter 14 Hands on hearts and fingers on pulses -- Index -- References.
Includes bibliographical references and index.
Keywords: School principals; Education -- Leadership; Teaching staff